Rabbit VX2 Liver Tumor Model: A Review of Clinical, Biology, Histology, and Tumor Microenvironment Characteristics - Pascale, Florentina; Pelage, Jean-Pierre; Wassef, Michel; Ghegediban, Saïda H.; Saint-Maurice, Jean-Pierre; De Baere, Thierry; Denys, Alban; Duran, Rafael; Deschamps, Frédéric; Pellerin, Olivier; Maeda, Noboru; Laurent, Alexandre; et al. (Frontiers in Oncology, 2022)
The rabbit VX2 is a large animal model of cancer used for decades by interventional radiologists to demonstrate the efficacy of various locoregional treatments against liver tumors. What do we know about this tumor in the new era of targeted therapy and immune-oncology ? The present paper describes the current knowledge on the clinics, biology, histopathology and tumor microenvironment of VX2 based on a literature review of 741 publications in the liver and in other organs. It reveals the resemblance with human cancer (anatomy, vascularity, angiogenic profile, drug sensitivity, immune microenvironment), the differences (etiology, growth rate, histology) and the questions still poorly explored (serum and tissue biomarkers, genomic alterations, immune checkpoint inhibitors efficacy).